(untitled) (The International Research Journal of Management Science, 2022)
Objectives – This paper investigates the impact of psychological workplace climate (PWC) on employee well-being (EWB). It also examines the moderating effect of emotional intelligence (EI) on the relationship of psychological workplace climate and overall employee well-being. Design/Methodology/Approach – Quantitative approach is used as a design involving a self-administrated questionnaire for data collection from 125 information technology professionals working in 7 different software development companies of Kathmandu Valley. Different analytical tools like correlation analysis, hierarchical regression, and one-way analysis of variance (ANOVA) tests are executed to test the proposed hypotheses. Findings – The results highlight the positive impact of psychological workplace climate on overall employee well-being and the moderating effect of emotional intelligence is evident in the relationships between independent and dependent variables. Practical Implications – These findings highlight that managers must consider psychological workplace climate while formulating organizational policies and strategies. It also serves as a guideline for IT managers to improve their emotional intelligence for the well-being of their employees. Originality/Value – The study depicts the high value of moderating variable - emotional intelligence and independent variable- psychological workplace climate on employee well-being, which is crucial knowledge to managers and chief executive officer (CEO) for building successful businesses.